2015
DOI: 10.1038/ejhg.2015.100
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of variants related to familial hypercholesterolemia in families with premature myocardial infarction

Abstract: Familial hypercholesterolemia (FH) is an oligogenic disorder characterized by markedly elevated low-density lipoprotein cholesterol (LDLC) levels. Variants in four genes have been reported to cause the classical autosomal-dominant form of the disease. FH is largely under-diagnosed in European countries. As FH increases the risk for coronary artery disease (CAD) and myocardial infarction (MI), it might be specifically overlooked in the large number of such patients. Here, we systematically examined the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 60 publications
2
35
0
11
Order By: Relevance
“…Recently APOE , which encodes apolipoprotein E that directs removal of chylomicron and very low-density lipoprotein remnants from the circulation, has been implicated in the pathogenesis of FH. 1113 Using family-based linkage analysis and whole exome sequencing, Fouchier et al 14 and Braenne et al 15 identified 5 variants in STAP1 , which has been proposed as the fourth gene causing FH. Affected individuals had a relatively mild FH phenotype.…”
Section: Pathogenesis and Geneticsmentioning
confidence: 99%
“…Recently APOE , which encodes apolipoprotein E that directs removal of chylomicron and very low-density lipoprotein remnants from the circulation, has been implicated in the pathogenesis of FH. 1113 Using family-based linkage analysis and whole exome sequencing, Fouchier et al 14 and Braenne et al 15 identified 5 variants in STAP1 , which has been proposed as the fourth gene causing FH. Affected individuals had a relatively mild FH phenotype.…”
Section: Pathogenesis and Geneticsmentioning
confidence: 99%
“…One of these is the GUCY1A3 locus 3 . Interestingly, only a few CAD risk loci, like those harboring LDLR and PCSK9 69 , contain mutations which were also found to co-segregate with CAD in a Mendelian pattern of inheritance. We have recently observed such allelic series at the GUCY1A3 CAD risk locus, for which a heterozygous loss-of-function allele was identified by linkage and a common variant by GWAS analysis to affect CAD risk, respectively 3,10 .…”
Section: Introductionmentioning
confidence: 99%
“…In the 2KJPN reference panel, we identified two reported pathogenic missense variants (Table 3). One of the variants, p.Arg3527Gln, is a well-characterized pathogenic missense variant [67] in APOB, and was identified in only one heterozygous individual among the 2049 individuals (allele frequency = 0.0002). Another missense variant, p. Ile3768Thr [68], was registered as DM in HGMD, and was identified in 2KJPN in a heterozygous individual.…”
Section: Apobmentioning
confidence: 99%